The Origin of High-velocity Stars Considering the Impact of the Large Magellanic Cloud - Jiwei Liao; Cuihua Du; Mingji Deng; Dashuang Ye; Hefan Li; Yang Huang; Jianrong Shi; Jun Ma (The Astronomical Journal, 2024)
Utilizing astrometric parameters sourced from Gaia Data Release 3 and radial velocities obtained from various spectroscopic surveys, we identify 519 high-velocity stars (HiVels) with a total velocity in the Galactocentric rest frame greater than 70% of their local escape velocity under the Gala MilkyWayPotential . Our analysis reveals that the majority of these HiVels are metal-poor late-type giants, and we show nine HiVels that are unbound candidates to the Galaxy with escape probabilities of 50%. To investigate the origins of these HiVels, we classify them into four categories and consider the impact of the Large Magellanic Cloud (LMC) potential on their backward-integration trajectories. Specifically, we find that one of the HiVels can track back to the Galactic center, and three HiVels may originate from the Sagittarius dwarf spheroidal galaxy (Sgr dSph). Furthermore, some HiVels appear to be ejected from the Galactic disk, while others formed within the Milky Way or have an extragalactic origin. Given that the LMC has a significant impact on the orbits of Sgr dSph, we examine the reported HiVels that originate from the Sgr dSph, with a few of them passing within the half-light radius of the Sgr dSph.